Anti‐tumour necrosis factor biological therapies for the treatment of uveitic macular oedema (UMO) for non‐infectious uveitis - Tallouzi, Mohammad O (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of anti‐TNF therapy for UMO.